Analysis of Income Income in Batam City Through the Tourism Industry - Ria Bintan Napitupulu; Andrea Putri; Fitri Fitri; Kendy Setiawan Hartono (Eduvest - Journal of Universal Studies, 2021)
Batam Islands has a strategic geographical location between various foreign countries such as Vietnam, Cambodia, Brunei Darussalam, Malaysia and Singapore. Therefore, competition in the Riau Islands is not centered on national competition, even in the international field, because of the geographical location of the Riau Islands which is closer to various foreign countries than the capital city of Indonesia and is also the third tourism destination after Bali and Jakarta. This research uses descriptive qualitative method. Primary data was obtained by conducting (a) in-depth interviews with relevant stakeholders in Batam City Regency. While secondary data comes from various trusted publications, such as BPS, Bappeda Belitung Regency, journals, newspapers, magazines, official documents, and other articles sourced from the internet. All the data is then compiled and adjusted to the focus of this study and then analyzed and drawn conclusions. The results of this study concluded that the economic decline in the Batam tourism sector was caused by these factors. (1) The rapid spread of covid-19 made Indonesia decide to close itself off from other countries. (2) the lack of foreign tourists who travel in Batam. (3) Batam has no plans to stabilize the economy when there are no foreign tourists.